Public Debt and Practical Problems Regarding the Use of the Prudence and Recovery Procedures - Duda, Mikołaj (Journal of Finance and Financial Law, 2014)
The goal of the article is to present actual problems regarding the definition of public debt in the polish financial law, its compliance with polish constitution and doubts surrounding the eventual usage of safety and prudence procedures in the context of public debt. The author expresses his concern about current regulations and believes that a quick legislator’s intervention is needed. Finally the article aims to analyze the newly introduced procedure about stabilizing national expenditure.